2020
DOI: 10.4236/health.2020.126046
|View full text |Cite
|
Sign up to set email alerts
|

Survival after Sexual Violence and Genocide: Trauma and Healing for Yazidi Women in Northern Iraq

Abstract: Introduction: In August 2014, the Yazidi community of Sinjar, in the Nineveh Governorate of Northern Iraq, was brutally targeted by the so-called Islamic State of Iraq and Syria (ISIS) for annihilation through murder, torture, and the systematic and premeditated use of rape and sexual slavery of Yazidi women. In 2016, the United Nations High Commissioner for Human Rights concluded that ISIS was committing genocide, crimes against humanity, and war crimes against Yazidis. Methods: Using current international li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
6
0
2
Order By: Relevance
“…It may be because sensationalized rape stories are not merely poor reporting examples but also an alarm call in terms of media critiques and social activities (Rekdal, 2017). Therefore, the overall role of newspapers in reporting child sexual abuse cases is positive (Goodman et al, 2020). Also, the publication of n = 64 cases within six months shows that newspapers are highly concerned about child welfare in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…It may be because sensationalized rape stories are not merely poor reporting examples but also an alarm call in terms of media critiques and social activities (Rekdal, 2017). Therefore, the overall role of newspapers in reporting child sexual abuse cases is positive (Goodman et al, 2020). Also, the publication of n = 64 cases within six months shows that newspapers are highly concerned about child welfare in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Feeling ‘safe to tell’, a mechanism previously reported by Spangaro ( 2015 ), is particularly important for Yazidi survivors of CRSV, where sexual relations with those outside of the community are condemned. Fear of discrimination has been attributed to suicide and mental illness (Goodman et al ., 2020 ). One study illustrated that 44.6% of formerly enslaved Yazidi females felt extremely excluded by community members, and 32.3% felt worried about not being able to get married or continue their marriage (Erdener, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the direct applicability is limited because of different age and population groups, it nonetheless highlights the importance social support and connection can play in fostering positive responses. A previous study on Yazidi women found that less social support (due to more time spent dislocated from family) and more experiences of sexual violence may increase perceived social rejection from the community due to humiliation and violation of family honor (Goodman et al, 2020). Indeed, in collectivist societies such as the Yazidis, the influence of systems such as the family, religion, and community can play both positive and negative influence on posttraumatic psychological outcomes (Nugent et al, 2014).…”
Section: Discussionmentioning
confidence: 99%